P–432 Do stage and grade of malignancy impact fertility preservation in breast cancer patients?. (6th August 2021) - Cioffi, R; Mangili, G; Sarais, V; Bergamini, A; Vanni, V S; Pagliardini, L; Signorelli, S; Cervini, L; Longo, V; Candiani, M; Papaleo, E
Abstract: Study question: Do stage and grade of breast cancer impact the number of retrieved mature oocytes during controlled ovarian stimulation for fertility preservation? Summary answer: Stage and grade of breast cancer do not impact the number of retrieved mature oocytes. Higher grade breast cancer requires higher gonadotropin doses during stimulation. What is known already: Cancer can impair ovarian response by unknown mechanisms. Some authors suggest that it could be detrimental on fertility because it elicits a catabolic state, increasing stress hormone levels. Some studies have also shown that ovarian response to controlled ovarian stimulation (COS) is, in some way, compromised in oncological patients. Little is known about the impact of different types of cancer on ovarian reserve, and specifically whether higher stage and grade could compromise egg retrieval during fertility preservation (FP) techniques. Study design, size, duration: Retrospective cohort study evaluating data of FP treatment cycles among women with breast cancer at the Oncofertility Unit of San Raffaele Hospital, Milan in the period from 2011 to 2019. Participants/materials, setting, methods: Inclusion criteria were: breast cancer diagnosis; age 22–41; oocyte cryopreservation after stimulation with a random start GnRH-antagonist protocol. Patients receiving chemotherapy before FP were excluded. We compared outcomes between low-stage (stage I) and high-stage (stage II-III) patients and low-grade (G1-G2) and high-grade (G3) patients. Main study outcome was the total number of retrieved mature oocytes. Univariate analysis was performed by Mann-Whitney test, Kruskal-Wallis test and Fisher's exact test. Multivariate analysis was performed by logistic regression. Main results and the role of chance: 101 stimulation cycles were included. High-stage disease patients were significantly younger than low-stage. Median antral follicle count (AFC) was 12 in low-stage and 10 in high-stage (age-adjusted p = 0.92) and median anti-mullerian hormone (AMH) levels were 1.9 ug/L in low-stage and 1.8 ug/L in high-stage (age-adjusted p = 0.22). No significant difference in stimulation protocols and follicle-stimulating hormone (FSH) start and total dose could be detected between the 2 groups. Median number of vitrified oocytes was 7 in both groups (p = 0.75). No significant difference could be observed in median AFC (13 vs 10, p = 0.14) and AMH levels (2.1 vs 1.5, p = 0.88) between low-grade and high-grade disease patients. When adjusting for age, AFC was found to be significantly lower in high-grade disease patients (p = 0.03). Patients with high-grade tumors were stimulated with higher doses of FSH (age-adjusted p-value=0.03). Median number of vitrified oocytes was 6 in low-grade patients and 7 in high-grade (p = 0.35). In a multivariate model including age, cancer stage, cancer grade and molecular classification, the only significant factor found to be inversely associated with AFC was cancer grade (OR 3.6; 95% CI 0.7 – 6.5, p = 0.01), while only age was significantly associated with oocyte retrieval (OR 0.4; 95% CI 0.01 – 0.9, p = 0.04). Limitations, reasons for caution: The main limitations of our study are its retrospective design and the small sample size. Wider implications of the findings: Fertility preservation counselling and ovarian stimulation protocols of breast cancer patients could be implemented with cancer grade. Trial registration number: Not applicable